A Computer-based 21st Century Prototype - Sangarun, Pannathon (Beyond Words, 2014)
Abstract This paper describes a prototype computer-based reading comprehension program. It begins with a short description, at a general level, of theoretical issues relating to the learning of comprehension skills in a foreign/second language learning. These issues cover such areas as personal meaning-making on the basis of individual differences and the need for individualized intervention to maximize the comprehension process. Modern technology facilitates this process and enables simultaneous support of large numbers of students. Specifically, from a learning perspective, the program focuses on students’ personal understandings while, from a reading perspective, the construction of meaning is based on an interactive model where both high-level (global, inferential) structures are elicited/studied as well as low-level structures (e.g. vocabulary, grammar). These principles are strengthened with research findings from studies in awareness and language processing based on eye-movement analysis. As part of its reading comprehensions focus, the system also has a strong commitment to the development of critical thinking skills, recognized as one of the most important 21st Century skills. The program is then described in detail, including its ability to store students’ responses and to be administered through standard learning management systems. Finally, an outline of planned future developments and enhancements is presented.